2012
DOI: 10.1073/pnas.1111670109
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic basis of pod corn ( Tunicate maize)

Abstract: Pod corn is a classic morphological mutant of maize in which the mature kernels of the cob are covered by glumes, in contrast to generally grown maize varieties in which kernels are naked. Pod corn, known since pre-Columbian times, is the result of a dominant gain-of-function mutation at the Tunicate ( Tu ) locus. Some classic articles of 20th century maize genetics reported that the mutant Tu locus is complex, but molecular details remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 34 publications
2
49
0
Order By: Relevance
“…These results support the hypothesis that SVP genes function downstream of TAW1. Interestingly, the ectopic expression of SVP genes in barley and maize also resulted in the severe suppression of SM identity, suggesting that SVP function might be conserved among grasses (34)(35)(36). In conclusion, our data indicate that TAW1 suppresses the acquisition of SM identity through the induction of SVP genes, which consequently promote or prolong BM identity.…”
Section: Taw1 Is Expressed In the Meristem To Suppress The Transitionmentioning
confidence: 56%
“…These results support the hypothesis that SVP genes function downstream of TAW1. Interestingly, the ectopic expression of SVP genes in barley and maize also resulted in the severe suppression of SM identity, suggesting that SVP function might be conserved among grasses (34)(35)(36). In conclusion, our data indicate that TAW1 suppresses the acquisition of SM identity through the induction of SVP genes, which consequently promote or prolong BM identity.…”
Section: Taw1 Is Expressed In the Meristem To Suppress The Transitionmentioning
confidence: 56%
“…Previously, genomic cloning recovered two Zmm19 genes in Tu1, known as Tu1-A and Tu1-B, and one gene each in Tu1-d, Tu1-l, and Tu1-md (Munster et al, 2004;Wingen et al, 2012). Sequence analysis indicated that both Tu1-l and Tu1-d were analogous to Tu1-B, whereas Tu1-md was analogous to Tu1-A.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis revealed that both Tu1-A and Tu1-B are structurally rearranged by insertion of a novel 2-kb Mu-like element in the 59 cis-regulatory region of Zmm19, which is fused with the 39 flanking region of an unknown gene (GRMZM2G006297) located on the other side of the 1.8-Mb interval from Zmm19 in the opposite orientation ( Figure 2B). This 1.8-Mb chromosomal inversion would be expected to inhibit recombination and likely accounts for the cold spot ( Figure 2A) that prohibited previous attempts to precisely map Zmm19 relative to Tu1 (Münster et al, 2002;He et al, 2004;Wingen et al, 2012). The analyses also revealed that Tu1-A is distinguished from Tu1-B by the presence of a 3.5-kb insertion in the first intron, a non-long terminal repeat retrotransposon ( Figure 2B, yellow triangle).…”
Section: Fine Mapping Of Tu1mentioning
confidence: 93%
See 2 more Smart Citations